Viral Infection in Enhance the Inflammatory Bowel Disease in Children: A Review: Infeksi Virus dalam Meningkatkan Penyakit Radang Usus pada Anak: Sebuah Tinjauan - Mohammad, Noor J.; Kadhim, Nuha Saeed; Shreef, Noor Salah (Universitas Muhammadiyah Sidoarjo, 2025)
Viral infections, which typically have a high rate of morbidity and mortality, are more challenging to identify. In particular, studies on rotavirus, hepatitis B virus, bacteriophages, enteric viruses, cytomegalovirus, and Epstein-Barr virus were evaluated for IBD. These results suggest that IBD patients are more likely to get viral infections. Therefore, medical practitioners should be more aware of the increased risk of viral infections in patients with inflammatory bowel disease. The incidence and prevalence of childhood-onset inflammatory bowel diseases (IBD), which include ulcerative colitis and Crohn's disease subtypes, have significantly increased in recent years, making them important pediatric chronic diseases on a global scale. Childhood-onset IBD is more widespread and dangerous than adult-onset IBD. The biological treatment for juvenile IBD is anti-tumor necrosis factor therapy, and more treatment options are urgently needed. Currently, this patient population is prescribed off-label other biologic medicines such as Steinman, and vedolizumab. Understanding the viral infection's causes, diagnosing and tracking the illness, treating patients, and managing the psychological and physical effects of having IBD are all crucial. Globally, the frequency of IBD varies greatly; estimates place the number of affected individuals at 2.2 million in Europe and 1.6 million in the United States. Highlights: Viral infections increase risk in IBD patients; awareness is crucial. Childhood-onset IBD is rising; better treatments are urgently needed. Global IBD cases exceed 3.8 million; management and diagnosis are vital. Keywords: Viral Infection, Enhanced, Inflammatory Bowel Disease